Does the market reaction to dividend news is influenced by investor sentiment? - Vieira, Elisabete F. Simões (2012)
We analyse whether the investor sentiment affects the market reaction to dividend change announcements. We use the European Economic Sentiment Indicator data, from Directorate General for Economic and Financial Affairs (DG ECFIN), as a proxy for investor sentiment and focus on the market reaction to dividend change announcements. Our results indicate that the investor sentiment have some influence on the market reaction to dividend change announcements, for two of the three analysed markets. Globally, we find no evidence of investor sentiment influencing the market reaction to dividend change announcements for the Portuguese market. However, we find evidence that the positive share price reaction to dividend increases enlarges with sentiment, in the case of the UK markets, whereas the negative share price reaction to dividend decreases reduces with sentiment, in the French market.